Modelling Conformational Flexibility in a Spectrally Addressable Molecular Multi‐Qubit Model System. (12th October 2022) - Rogers, Ciarán J.; Asthana, Deepak; Brookfield, Adam; Chiesa, Alessandro; Timco, Grigore A.; Collison, David; Natrajan, Louise S.; Carretta, Stefano; Winpenny, Richard E. P.; Bowen, Alice M.
Abstract: Dipolar coupled multi‐spin systems have the potential to be used as molecular qubits. Herein we report the synthesis of a molecular multi‐qubit model system with three individually addressable, weakly interacting, spin 1 / 2 1/2 centres of differing g ‐values. We use pulsed Electron Paramagnetic Resonance (EPR) techniques to characterise and separately address the individual electron spin qubits; Cu II, Cr7 Ni ring and a nitroxide, to determine the strength of the inter‐qubit dipolar interaction. Orientation selective Relaxation‐Induced Dipolar Modulation Enhancement (os‐RIDME) detecting across the Cu II spectrum revealed a strongly correlated Cu II ‐Cr7 Ni ring relationship; detecting on the nitroxide resonance measured both the nitroxide and Cu II or nitroxide and Cr7 Ni ring correlations, with switchability of the interaction based on differing relaxation dynamics, indicating a handle for implementing EPR‐based quantum information processing (QIP) algorithms. Abstract : Systems with weak dipolar interactions have the potential to be used for molecular quantum computing. Orientation selective pulsed EPR was used to model the conformational flexibility of a molecular multi‐qubit model system. Spectrally addressable centres allowed for the individual manipulation of each spin qubit, while differing relaxation dynamics resulted in a proposed handle for the implementation of quantum algorithms.